Trophic ecology of midwater zooplankton along a productivity gradient in the Southeast Pacific - Igor Fernández-Urruzola; Antonio Bode; Natalie Loick-Wilde; Wolfgang Schneider; Wolfgang Schneider; Dhugal Lindsay; Ruben Escribano; Ruben Escribano (Frontiers in Marine Science, 2023)
The environmental regulation of planktonic food web structure is a key determinant for the efficiency of energy transfer through trophic levels, with direct implications for the amount of energy that is available to top-consumers and deep-sea communities. Yet, the complex trophic interplay between the different components of plankton communities under contrasting environmental conditions remains unresolved. Here, we present a comprehensive field study based on compound-specific isotope analysis of amino acids that aims to explore depth-resolved changes in the trophic strategies of various size-classes of mesozooplankton from distinct habitats across the Southeast Pacific. According to the δ15N values of the so-called source amino acids such as phenylalanine, we first identified a clear shift in nitrogen sources for biological production, from nitrate in the productive upwelling waters of the Humboldt Current System to increased inputs of diazotroph-N within the ultra-oligotrophic South Pacific gyre. These shifts in the productivity and in the source of N at the base of the food web were not accompanied by significant changes in the trophic position (TP) of mesozooplankton, which were mainly omnivores (TP = 2.8 ± 0.3, n = 65) in all ecoregions. However, although the planktonic food web length remained relatively unaltered along the productivity gradient, the microbial contribution to mid-trophic level consumers appeared to be more important at relatively high productivities, likely due to more intense remineralization processes in a late successional stage of the upwelling throughout the coastal-transition zone. Altogether, this research work will contribute to a better understanding of the food web functioning in one of the least explored marine regions of the world’s oceans.